Perception of uncertainty concerning illness and coping styles among parents of children with central nervous system tumors: a correlation analysis - Lan, Bai; Qinqin, Zhao; Ying, Li; Zhihuan, Zhou (Frontiers in Pediatrics, 2025)
PurposeTo investigate the perception of uncertainty concerning illness among parents of children with central nervous system tumors and their coping styles and to analyze correlations to provide a basis for developing targeted intervention measures.MethodsWe studied 108 parents of children with central nervous system tumors admitted from January 2023 to January 2024. Information about these children and their parents were analyzed using the modified Parents' Perception of Uncertainty in Illness Scale (PPUS) and the Coping Health Inventory for Parents to calculate correlations of parents' perceptions of uncertainty concerning illness and coping styles.ResultsThe total score of PPUS was 45.28 ± 8.428 for the parents of children. The most common coping styles were the maintenance of family unity, cooperation, and optimism. The correlation analysis revealed that parents' perception of uncertainty concerning illness negative correlated with coping style (p < 0.05).ConclusionThe parents of children with central nervous system tumors show substantial perception of uncertainty concerning the illness and are susceptible to lack of communication and expression. Positive, effective coping methods should be adopted to reduce uncertainty concerning illness to reduce the psychological pressure on parents.